Left bundle branch area pacing prevents pacing induced cardiomyopathy in long‐term observation - Bednarek, Agnieszka; Kiełbasa, Grzegorz; Moskal, Paweł; Ostrowska, Aleksandra; Bednarski, Adam; Sondej, Tomasz; Kusiak, Aleksander; Rajzer, Marek; Jastrzębski, Marek (Pacing and clinical electrophysiology, 2023)
Background Left bundle branch area pacing (LBBAP) is one of the methods to deliver conduction system pacing which potentially avoids the negative impact of conventional right ventricular pacing. Objective To assess echocardiographic outcomes in a long‐term observation in patients with LBBAP implemented for bradyarrhythmia indications. Methods and Results A total of 151 patients with symptomatic bradycardia and LBBAP pacemaker implanted, were prospectively included in the study. Subjects with left bundle branch block and CRT indications (n = 29), ventricular pacing burden <40% (n = 11), and loss of LBBAP (n = 10) were excluded from further analysis. At baseline and the last follow‐up visit, echocardiography with global longitudinal strain (GLS) assessment, 12‐lead ECG, pacemaker interrogation, and blood level of NT‐proBNP were performed. The median follow‐up period was 23 months (15.5–28). None of the analyzed patients fulfilled the criteria for pacing induced cardiomyopathy (PICM). Improvement in left ventricular ejection fraction (LVEF) and GLS was observed in patients with LVEF <50% at baseline (n = 39): 41.4 ± 9.2% versus 45.6 ± 9.9%, and 12.9 ± 3.6% versus 15.5 ± 3.7%, respectively. In the subgroup with preserved EF (n = 62), LVEF and GLS remained stable at follow‐up: 59.3 ± 5.5% versus 60 ± 5.5%, and 19 ± 3.9% versus 19.4 ± 3.8%, respectively. Conclusion LBBAP prevents PICM in patients with preserved LVEF and improves left ventricle function in subjects with depressed LVEF. LBBAP might be the preferred pacing modality for bradyarrhythmia indications.